CSR, From Perception to Role in Performance: A Case Study of SMEs in Industrial Estate Peshawar, Pakistan - Waqar Ahmad; Shahnawaz Khan (International Journal of Experiential Learning & Case Studies, 2019)
This paper explores the perception and role of corporate social responsibility (CSR) in the performance of small and medium enterprises (SMEs) of Industrial Estate Peshawar, Pakistan. Philosophically the study had a subjective ontology; and therefore, a subjective epistemological stance leading to interpretivism as its core theoretical position.  To inquire into the perception and role of CSR in SME’s, the study utilized Yin’s case study model thus collecting data through qualitative semi-structured interviews and observations. Further, the study used Miles and Huberman (1994) approach of thematic modelling for the analysis of the data. The findings reveal that SMEs are somehow practising CSR in an informal manner. Surprisingly, CSR at strategic Level is missing. CSR practices towards employees are missing except health and safety measures.  Most of the firms contribute in an irregular manner to the local community -  training the locals, hiring them as internees, giving charity and donations, and purchasing of local supplies when available and feasible. While, except for one firm, the production or manufacturing firms have no environmental implications.  The firms are ethical in dealing with customers and suppliers, they offer customers a quality product which is the reason behind their performance in terms of sales or reputation. The only ethical factor of CSR has a role in SMEs performance.